Molecular Characterization of Cressa cretica L. Using SCoT and ISSR Markers - Mozhdeh Jahangir; Fatemeh Nasernakhaei (Journal of Genetic Resources, 2025)
Cressa cretica L. (Convolvulaceae) is a halophytic species with remarkable adaptability to saline environments, holding significant ecological and economic value. In this study, we conducted a comprehensive assessment of genetic diversity and structure in thirteen accessions collected from the eastern and western sides of the Karun River in Ahvaz, Iran. Two types of molecular markers, start codon targeted (SCoT) and inter-simple sequence repeat (ISSR), were employed to detect genetic variation and patterns of differentiation between geographical groups. Ten SCoT primers produced 92 amplified fragments, 87.9% of which were polymorphic, while ten ISSR primers generated 114 fragments with 85.6% polymorphism. Most of the genetic variation was found within groups rather than between them, indicating low genetic differentiation. Although both UPGMA and PCoA analyses grouped the accessions into two main clusters, these clusters did not correspond clearly to their geographical origins. Bayesian model-based grouping revealed three genetic subgroups with SCoT data, while ISSR data supported two subgroups, suggesting a higher resolution of SCoT markers in detecting subtle genetic subdivisions. Although ISSR markers displayed higher average values for polymorphism information content, Nei's gene diversity, and Shannon’s index, the ability of SCoT markers to uncover finer genetic structures highlights their complementary role. These results indicate moderate differentiation with significant gene flow among accessions, likely influenced by both reproductive strategies and local environmental conditions. The combined use of both marker systems provided a more comprehensive picture of genetic variation in this salt-tolerant species. These findings provide valuable baseline information for future conservation efforts and sustainable utilization of C. cretica in saline ecosystems.